The Saber of Alexey Apostol from Collection of Museum in Mirohorod. A Historical Study of a Weapon - Toichkin, Denys (Narzędzia wojny, 2023)
The article presents a thorough study of the unique saber of 17th century, that kept in the Mirhorod Local Lore Museum (Ukraine). The form of blade of this ‘Hussar’ saber represents a special mix of Ottoman and Eastern European weaponry traditions of the Early Modern Times. After a comprehensive analyze of the inscriptions on the blade, the author interpreted them as the name of the owner of weapon, inscription year, didactic sentence and bind them up with the real historical events and persons, known from the written sources. This saber is important for analyzing and illustrating the development of Eastern European blades, and recognized as a very rare sample, that belonged to the Alexey Apostol – a high-ranking Cossack noble of polk (province) of Mirhorod.